2014
DOI: 10.1016/j.meatsci.2013.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of amino acids and biogenic amines throughout storage in sausages made of horse, beef and turkey meats

Abstract: The changes in concentration of free amino acids and biogenic amines, along 28 d of storage at 4 °C, were monitored in a wide range of European ripened sausages manufactured from horse, beef and turkey meats. Generally speaking, both chemical families became more concentrated with elapsing time -but rather distinct patterns were followed in each meat type: total free amino acids increased by 13-fold in the case of horse sausages, and 5-fold in the case of beef sausages, but decreased to one third in the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 54 publications
7
38
0
1
Order By: Relevance
“…tyrosine and arginine were also reported by other researchers, especially during the extended ripening of dry-cured ham www.food.actapol.net/ (Alfaia et al, 2004). A gradual release of amino acids throughout ageing is typical in dry fermented meat products (Rabie et al, 2014;Stadnik and Dolatowski, 2015). Such increasing trends were typically observed for all study samples, and are consistent with reports by Stadnik and Dolatowski (2015).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…tyrosine and arginine were also reported by other researchers, especially during the extended ripening of dry-cured ham www.food.actapol.net/ (Alfaia et al, 2004). A gradual release of amino acids throughout ageing is typical in dry fermented meat products (Rabie et al, 2014;Stadnik and Dolatowski, 2015). Such increasing trends were typically observed for all study samples, and are consistent with reports by Stadnik and Dolatowski (2015).…”
Section: Resultssupporting
confidence: 90%
“…In the present study, these amino acids exhibited increases for lysine and histidine and decreases for tyrosine for all samples respectively after 36 months of ageing. Rabie et al (2014) also reported considerable increases throughout storage of these three FAAs in the case of fermented horse meat and only one of them (lysine) in the case of beef products. The TFAA content was higher for the salted beef sample (S) and the cured one (N) compared with salted beef marinated with acid whey (W) after 21 days and 36 months of ageing.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Rabie et al (2014) analyzed the evolution of each amino acid as well as the total free amino acid contents in sausages made of horse meat, beef, and turkey meats.…”
Section: Free Amino Acid Contentsmentioning
confidence: 99%